The United States and the New Regionalism/ Bilateralism - Yang, Yongzheng; Hilaire, Alvin (Washington, D.C. : International Monetary Fund, 2003)
Current U.S. trade policy stresses establishing free trade areas (FTAs) with partners spanning the globe. Motivations include enhancing goods and services trade; stimulating investment flows; extending standards on intellectual property rights, labor, and the environment; and addressing geopolitical concerns. Simulations of FTAs with the United States highlight the importance of trade complementarity, trade diversion, and welfare losses for nonmembers. Agriculture and textiles play a central role in determining welfare outcomes. Initial improvement in market access enjoyed by participants could be eroded progressively as global liberalization proceeds, and this preference erosion might act as a disincentive to participate in multilateral liberalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet